Study of chloroplatinic acid sorption by modified carbon materials - S. V. Golovizin; M. L. Levchenko; V. S. Trubin; N. A. Salanov; N. A. Serkova (Тонкие химические технологии)
The influence of oxidation and impregnation of the carbon materials on the sorption of H2PtCl6 was studied. The state of platinum on the surface was studied with the SEM, EDS, XPS and XAFS methods.